The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1302/0301-620x.102b12.bjj-2019-1136.r3
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in orthopaedic oncology

Abstract: Aims Malignancy and surgery are risk factors for venous thromboembolism (VTE). We undertook a systematic review of the literature concerning the prophylactic management of VTE in orthopaedic oncology patients. Methods MEDLINE (PubMed), EMBASE (Ovid), Cochrane, and CINAHL databases were searched focusing on VTE, deep vein thrombosis (DVT), pulmonary embolism (PE), bleeding, or wound complication rates. Results In all, 17 studies published from 1998 to 2018 met the inclusion criteria for the systematic review. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
2
23
2
Order By: Relevance
“…The study by Yamaguchi et al, identified age > 70 years as a risk factor for VTE events in 94 patients undergoing musculoskeletal tumor resection 98 . In contrast, other studies were not able to detect an association between age and VTE occurrence 96,97,99,100 .…”
Section: - Is There a Correlation Between Age And The Risk Of Vte In ...mentioning
confidence: 66%
See 3 more Smart Citations
“…The study by Yamaguchi et al, identified age > 70 years as a risk factor for VTE events in 94 patients undergoing musculoskeletal tumor resection 98 . In contrast, other studies were not able to detect an association between age and VTE occurrence 96,97,99,100 .…”
Section: - Is There a Correlation Between Age And The Risk Of Vte In ...mentioning
confidence: 66%
“…The influence of age on VTE risk in patients with fractures of the lower extremity and oncologic orthopaedic surgeries were not consistent 92-101 . In patients undergoing surgical treatment of fractures below the hip, age ≥ 60 years was identified as a risk factor for VTE (RR 1.85 [95% CI 1.34 - 2.55]) in 191,294 patients 92 .…”
Section: - Is There a Correlation Between Age And The Risk Of Vte In ...mentioning
confidence: 94%
See 2 more Smart Citations
“…Rationale: Major orthopaedic surgeries and oncological patients have increased risk for VTE, with the mean incidence of all VTE events in orthopaedic oncology patients being 10.7% (1.1% to 27.7%). Risk factors for increased events include endoprosthetic replacements, hip and pelvic resections, surgical procedures taking longer than 3 hours, and chemotherapy 14 , all of which are common with sarcoma surgeries. Higher preoperative white blood cell count (odds ratio [OR] 1.15, 95% confidence interval [CI] 1.01-1.29) and post-operative wound complications (OR 5.01, 95% CI 1.93-13.55) were found to be independent risk factors for VTE 15 .…”
Section: - For Primary Bone Tumours/sarcoma Patientsmentioning
confidence: 99%